Sistema especialista para identificação do método de custeio para a formação do preço de venda - Zahaikevitch, Everaldo Veres (2014)
This research aimed to establish, through the use of a Specialist system – SS, the most viable costing method for the pricing of a particular product or service, in the cost accounting area. The system used was developed through a set of variables identified with the in-depth study of the most commonly used methods to establish sales price: Absorption Costing, Variable, Standard or ABC. The variables were transformed into questions and organized into five trees of possibilities grouped in four questions. For each question, there is an answer of yes or no type. From the tree of possibilities, the rules were created and subsequently implemented in a Shell to SS called Expert Sinta, free software. The system validation was performed comparing the tree of possibilities created manually with the tree generated by the Shell. The research is classified in applied, as for the nature; exploratory, for the goals and procedures, in bibliographical and experimental. This work was divided into six main activities: definitions of costing methods, selection of tool to implement the SS, identifying questions, elaborating the tree of possibilities, implementation and validation of SS. The results obtained with the developed SS allow the correct diagnosis, according to previously-deployed knowledge, aiming to be more accurate and responsive than human experts, but dependent on this for powering the system. This way, the SS can assist in the decision-making process, in the company maintenance in a competitive market.